Metabolomic analysis of halotolerant endophytic bacterium Salinivibrio costicola isolated from Suaeda maritima (L.) dumort - Lee, Jaeyoun; Um, Soohyun; Kim, Seung Hyun (Frontiers in Molecular Biosciences, 2022)
In this study, the Salinivibrio costicola strain was isolated from Suaeda maritima (L.) Dumort. collected in Sinan, Republic of Korea. The endophytic characteristics of the Gram-negative bacterium S. costicola were verified with metagenomics sequencing of S. maritima. S. costicola was cultivated for 3 days in a liquid medium with 3.3% sea salt and analyzed the metabolites produced by the strain cultured in five different bacterial cultivation media. From the bacterial cultures, polyhydroxybutyrate derivatives were detected using high-resolution mass spectrometry, and three major compounds were isolated by high-performance liquid chromatography. The chemical structures of the compounds were elucidated using nuclear magnetic resonance and MS analyses. The relationship between the compounds was confirmed with Global Natural Product Social Molecular Networking, which showed clustering of the compounds. From the S. maritima extract, polyhydroxybutyrate derivatives produced by S. costicola were detected as being accumulated in the host plant.